Spatial distribution and environmental risk assessment of hazardous elements (As, Hg, Pb, Cd, Cu, Cr, Zn, and Se) in wetland soils of Yellow Sea coastal area, Eastern China. Issue 1 (1st January 2021) - Zhou, Feng; Gu, Haixin; Li, Yuqi; Tang, Yufei; Ding, Ying; Sun, Jianxiong; Luo, Ting
ABSTRACT: The spatial distribution and environmental risk assessment of eight hazardous elements in wetland soils in Yellow Sea coastal area of China were investigated. The concentrations of As, Hg, Pb, Cd, Cu, Cr, Zn, and Se varied between 6.35-46.14, 0.004-0.05, 18.90-62.07, 0.17-3.76, 11.34-76.79, 21.52-80.88, 39.25-136.86, 0.002-0.16 mg/kg, respectively. The spatial distributions analysis demonstrated that the high levels of As, Pb, Cd, and Zn were in Sheyang area. The results of correlation and PCA indicated that natural and anthropogenic source were major sources for Pb, Cr, Cu, Zn, and Se. As and Cd were from industrial and agricultural sources, and Hg was from natural source. The Cd  indicated that 84% of sites experienced moderate and considerable contamination. The PER indices indicated that 68% of sites experienced considerable and high ecological risk. This study suggested that more attention should be paid to hazardous elements contamination of wetland soils in eastern China.